The design, synthesis and evaluation of aryl guanidinium derivatives as α2 adrenoceptor antagonists for the treatment of depression - Kelly, Brendan (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
Depression is among the leading causes of illness worldwide and is predicted to be the single largest contributor by 2020. Antidepressants are the most effective treatment but current drugs have slow onset of effects and are only successful for some individuals. The a2-adrenoceptor (a2-AR) has emerged as a promising target for the development of improved antidepressants with faster onset of action and reduced side effects. It is found in increased density and hyperactive conformation in the brains of depressed patients and its activation leads to: decreased monoamine levels in the brain, and reduced hippocampal neurogenesis and ceil survival, both now seen as fundamental causes of depression. Antagonists have been shown to reverse these effects and, more importantly, lead to antidepressant effects. However, their discovery has been hampered by the lack of a crystal structure of the a2-AR and the conflicting pharmacological profile of structurally similar ligands at the receptor. This project employed a ligand-based drug design strategy to identify the requirements for high binding affinity and antagonistic activity at the a2-AR for aryl guanidinium type molecules. The initial target pyridinyl guanidiniums were first studied computationally, then experimentally after synthesis, and finally were tested for affinity and activity at the a2-AR. A full theoretical description of the π-cation and π-π complexes available to the initial ligands was also carried out to model interactions with aromatic amino acid residues thought to be important in the active site, and several structure activity relationships could be drawn.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.